2022
DOI: 10.3390/foods11152250
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Anti-Inflammatory Effects of Extracts from Pulsed Electric Field-Treated Artichoke By-Products in Lipopolysaccharide-Stimulated Human THP-1 Macrophages

Abstract: In this study, pulsed electric field (PEF—3 kV/cm; 5 kJ/kg) pretreatment was used to intensify the extractability of valuable intracellular compounds from artichoke by-products during a subsequent aqueous extraction (solid–liquid ratio = 1:10 g/mL, T = 20 °C; t = 120 min). Total phenolic content (TPC), antioxidant activity (DPPH, ABTS) and HPLC–PDA analysis of the artichoke extract (AE) and the biological effects on human cell lines were determined. Chlorogenic acid was found to be the most abundant phenolic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 67 publications
1
11
0
Order By: Relevance
“…with broad antioxidant properties, as confirmed by the good free radical scavenging properties highlighted in the DPPH assay (IC 50 20.04 ± 2.52 µg/mL). These results confirmed the higher radical scavenger activity of wild artichoke with respect to the cultivated forms (globe artichoke) [ 33 , 34 ].…”
Section: Discussionsupporting
confidence: 76%
“…with broad antioxidant properties, as confirmed by the good free radical scavenging properties highlighted in the DPPH assay (IC 50 20.04 ± 2.52 µg/mL). These results confirmed the higher radical scavenger activity of wild artichoke with respect to the cultivated forms (globe artichoke) [ 33 , 34 ].…”
Section: Discussionsupporting
confidence: 76%
“…Considering the critical role of intestinal macrophages in maintaining GI tract homeostasis, recent research has highlighted the significance of these immune cells. Disruptions in macrophage abundance and function have been associated with the disturbances in gut homeostasis, leading to chronic inflammation associated with various GI diseases [ 39 , 50 , 51 ]. Based on these findings, it is suggested that artichoke extract may indirectly contribute to GI homeostasis by influencing intestinal macrophages, implying a potential avenue for further investigation.…”
Section: Inflammatory and Gastrointestinal Diseases And Artichokementioning
confidence: 99%
“…Anti-inflammatory action [36] Antimicrobial action [37] Di-caffeoylquinic acids 1,3-di-CQA Hepato-protective action [5] Anti-inflammatory action [38,39] Di-caffeoylquinic acids 1,5-di-CQA Antiglycative action [40] Di-caffeoylquinic acids…”
Section: -O-caffeoylquinic Acid 4-o-caffeoylquinic Acid 5-o-caffeoylq...mentioning
confidence: 99%
“…For example, good results were registered for an aqueous stem extract obtained by applying the pulsed electric field (PEF) treatment (used to increase the cell membrane permeability and disruption). This extract, mainly rich in 5-CQA (54%), reduces the effect on the expression and secretion of Interleukin-6 (IL)-6 and monocyte chemoattractant protein (MCP)-1/C-C motif chemokine ligand 2 (CCL2) in human THP-1 macrophages, when used as an inflammatory cell model [77]. A strong reduction in prostaglandins and other inflammatory mediators (C-reactive protein-CRP) and fibrinogen), and in the migration of inflammatory cells, was registered for a bract ethanolic extract.…”
Section: Anti-inflammatory and Antioxidant Activitiesmentioning
confidence: 99%